Aspectos estruturais e subjectivos dos espaços políticos em África: introdução a um debate - Franz-Wilhelm Heimer (Cadernos de Estudos Africanos)
The introduction by the editor of this issue informs about the international conference which originated the collection of papers presented here. It tries to locate these studies in the context of the international debate on the structure of, and changes in, politics in Africa. Distinguishing between the discussion on structure and that on the subjective dimension, it refers to what seems to be in this context the core contribution of each article. It points out the merits as well as the limitations of the collection and emphacises the importance of continuous and intensified empirical research articulated with a theoretical elaboration aimed at overcoming the present shortcomings in this field.